PENGELOLAAN RETRIBUSI PARKIR DI TEPI JALAN UMUM PERSPEKTIF SIYASAH SYAR’IYYAH - Nurfalita, Zavira; Sastrawati, Nila (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This study aims to examine how the management of parking levies on public roadsides, especially in Makassar City from the perspective of siyasah syar’iyyah. The method used is field qualitative research with a juridical and normative approach to syar’i. The management of public roadside parking in Makassar City shows that management has not been effective, sometimes even a source of congestion. This can be seen from the many violations of parking, such as the conversion of the shoulder of the road into a parking lot, illegal parking, and the lack of firmness in law enforcement. In the muamalah concept, the withdrawal of the parking levy by the official parking attendant can be matched with a storage system (wadi’ah) which allows for a deposit fee.